How Do Banks Serve SMEs? Business and Risk Management Models - de la Torre, Augusto; Martínez Pería, María Soledad; Politi, María Mercedes; Schmukler, Sergio L.; Vanasco, Victoria (World Bank, Washington, DC, 2013)
This study describes the business and risk management practices that banks use to serve small and medium enterprises (SMEs). To do so, we use recently collected evidence from Argentina and Chile for a significant number of banks in each country, gathered through on-site meetings, a tabulated questionnaire, and a detailed data request. We find that banks are setting up separate departments to serve the segment, targeting many SMEs from all economic sectors and geographic regions. Banks use relationship managers to seek out new clients. Risk management and loan approval is separate from sales, mostly centralized, but not largely automated. Knowing the client is still crucial to minimize risks. Overall, the patterns we uncover suggest that banks are in the middle of an on-going learning process, by which they are developing the structure to deal with SMEs in a sustainable basis over the coming years.